From lobbying to corruption: the strategies of interest groups to influence the law-making process. - Carraro Rossetto, Patricia (SPRINGER, 2021)
There is a widespread view that interest groups are key features of contemporary democracies. Through those political participation channels, citizens articulate their political preferences and interests, express their support and demands to the government, and seek to influence the public decision-making process. Interest groups with ambitions to influence public policy can choose from a wide range of strategies to accomplish this aim. Therefore, the purpose of this article is threefold. On the one hand, to shed some light on the strategies used by interest groups to influence the democratic law-making processes. On the other hand, to offer useful insights into the relationship and differences between lobbying, political financing, and corruption. Finally, to offer some brief comments on the measures proposed by the OECD to prevent undue and corrupt influence on decisionmakers. The article is based on three main assumptions. First, private organized interests seeking to influence the policy-making process is part of the complex political game. Second, lobbying is deemed as an intrinsically legitimate political action, even though it shall be carefully regulated by legislation for the sake of transparency, openness, and accountability. Three, corruption is defined as the abuse of entrusted power for private gain and the criminal offences included in this concept range from bribery to trading in influence.
Keywords: Participación política; Political participation; Interest groups; Lobbying; Political financing; Political corruption; OECD recommendations